FAKTOR YANG MEMPENGARUHI KEPEMIMPINAN KGPAA MANGKUNAGORO IX DAN KGPAA MANGKUNAGORO X DALAM PENGUATAN CITY BRANDING KOTA SURAKARTA - Fauzia, Vionna Ariella; Roychansyah, Muhammad Sani (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2025)
Solo the Spirit of Java is the city branding of Surakarta, which highlights its role as a cultural city. The implementation of Surakarta’s city branding cannot be separated from the involvement of several key actors, one of which is cultural institutions. Puro Mangkunegaran, as one of the iconic symbols of Javanese culture in Surakarta, plays a significant role in preserving and educating the public about Javanese culture. Various efforts have been made by Puro Mangkunegaran to innovate cultural preservation strategies in order to attract tourists and increase the number of tourist visits. This study is limited to the period from 2008 to 2024, starting from the official adoption of the city branding by the City of Surakarta. The research aims to identify the factors that influence the leadership of KGPAA Mangkunagoro IX and KGPAA Mangkunagoro X in strengthening the city branding of Surakarta. The research method applied is a case study with a holistic single-case design. The analysis reveals that several identified factors, when compared with existing propositions, indicate both similarities and new additions regarding the factors that influence the leadership of KGPAA Mangkunagoro IX and KGPAA Mangkunagoro X. There are both similarities and differences in the identified influencing factors during the leadership periods of KGPAA Mangkunagoro IX and KGPAA Mangkunagoro X.